THE EFFECTIVENESS OF SONGS USED FOR TEACHING CONDITIONAL SENTENCES (ELang | An English Language Education Journal, 2016)
The title of the research paper was “The Effectiveness of Songs Used forTeaching Conditional Sentences”. The study was conducted on the 16th ofSeptember 2015 until 23rd of September 2015. The objectives of the study wereto find out whether or not the songs were effective used for teaching conditionalsentences and to find out what were students responses toward the songs. Themethod that was used in this research was pre-experimental design. There wasonly one group to be researched. The sample was the second grade students ofSMA 1 Majalaya that consists of 41 students. The instruments were test andquestionnaire. The research findings were the value of t. was higher than the t.table (19.818 > 2.02). it could be put forward that songs were useful forimproving grammatical mastery especially in the first conditional sentences andthe second conditional sentences. The Null Hypotheses (H0) was rejected andthe Alternative Hypotheses (Ha) was accepted, stating that there was significantdifference in the result of students scores before and after the treatment usingsongs. It can be put forward that the use of songs for teaching conditionalsentences to the second grade of SMA 1 Majalaya was effective. Then the writerfound out that the students liked being taught conditional sentences by usingsongs. It was shown by the result of the questionnaire that 89% of studentsanswered that they really liked being taught by using songs. And 94% ofstudents anwered that the atmosphere of the class became enjoyable. Based onthe result that has been found by the writer, it can be put forward that songs areeffective used for teaching conditional sentences and the students’ responses aregood and positive.